Методика врахування динаміки приводу при складанні моделі механізму з паралельною кінематикою - Мельніченко, М. М.; Мірошніченко, М. С.; Бєляєв, Ю. Б.; Melnychenko, N.; Belyaev, U.; Miroshnichenko, M. (КНТУ, 2013)
В статті розв’язано актуальну задачу розробки моделі динаміки механізму з паралельною кінематикою побудованого на базі платформи Хью-Стюарта з приводами від вентильних двигунів. Отримані результати можуть бути використані для керування механізмами подібного типу. The purpose of this paper is to model the dynamics of certain generalized control object "engine platform" as a system of differential equations that relates the change voltages applied to the valve actuators, as amended coordinate center of mass platform. In the article studied the dynamics of the actual problem with parallel kinematics mechanism now can not Hugh Stewart. The results can be used to control equipment built on the basis of a similar type. Thus the combination of known dynamics equations platform-Hugh Stewart and information about the transfer function for brushless signal control and a torque on the shaft resistance, yielded the relationship between the change in voltage control input and coordinate motor center of mass of the platform.
The treatment of the dynamics of the drive mechanism in the model to be parallel kinematics
Keywords: динаміка; гексапод; вентильні приводи; dynamics; hexapod; valve actuators